Skrining Tingkat Pengetahuan Penyakit Ginjal Kronis Pada Masyarakat Di Wilayah Kerja Puskesmas Bangkala - Imran Pashar; Sudirman Efendi; Sardi Anto (Jurnal Informasi Pengabdian Masyarakat, 2023)
Chronic kidney disease is a chronic disease and has a progressive decline in kidney function over several months or years. Chronic Kidney Disease (CKD) is a progressive disease of worsening kidney function that occurs over several months to years characterized by gradual changes in normal kidney structure with fibrotic tissue. This type of community service begins at the stage of community knowledge assistance regarding the level of knowledge of chronic kidney disease. The method used is descriptive quantitative analytic which will see an overview of community knowledge using a questionnaire and the results of this activity will be the basis for carrying out further activities. The location of the Community Service is carried out in the work area of the Bangkala Health Center which is located on Jalan Tamangapa Raya 3 which is in the work area of the Bangkala Health Center, Makassar City, namely RW 7B Bangkala Village, Manggala District, Makassar City in collaboration with Bangkala Health Center officers. This activity was focused on 40 people who have a history of hypertension or diabetes mellitus. the results found that the average knowledge related to chronic kidney failure was in the less category of 77.5%. It is hoped that the community can increase knowledge regarding chronic kidney failure (CKD) from various existing sources in order to prevent the occurrence of CRF in patients who have a history of hypertension or diabetes mellitus